Identification and Tracking of Alloreactive T Cell Clones in Rhesus Macaques Through the RM-scTCR-Seq Platform - Gerdemann, Ulrike; Fleming, Ryan A.; Kaminski, James; McGuckin, Connor; Rui, Xianliang; Lane, Jennifer F.; Keskula, Paula; Cagnin, Lorenzo; Shalek, Alex K.; Tkachev, Victor; Kean, Leslie S. (Frontiers in Immunology, 2022)
T cell receptor clonotype tracking is a powerful tool for interrogating T cell mediated immune processes. New methods to pair a single cell’s transcriptional program with its T cell receptor (TCR) identity allow monitoring of T cell clonotype-specific transcriptional dynamics. While these technologies have been available for human and mouse T cells studies, they have not been developed for Rhesus Macaques, a critical translational organism for autoimmune diseases, vaccine development and transplantation. We describe a new pipeline, ‘RM-scTCR-Seq’, which, for the first time, enables RM specific single cell TCR amplification, reconstitution and pairing of RM TCR’s with their transcriptional profiles. We apply this method to a RM model of GVHD, and identify and track in vitro detected alloreactive clonotypes in GVHD target organs and explore their GVHD driven cytotoxic T cell signature. This novel, state-of-the-art platform fundamentally advances the utility of RM to study protective and pathogenic T cell responses.